Pengaruh Ukuran Perusahaan, Likuiditas, Dan Konservatisme Akuntansi Terhadap Kualitas Laba - Rahmadini Safitri; Mayar Afriyenti (Universitas Negeri Padang, 2020)
The study aims to test empirically the effect of firm size, liquidity, and accounting conservatism of earnings quality. This study uses a quantitative approach with a causal associative research type. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. By using the purposive sampling method, 155 samples were selected. Earnings quality is measured by regressing the CAR value (Narita, 2020). Company size is measured by LogSize. Liquidity is measured using the current ratio. And accounting conservatism is measured using the Givoly and Hayn (2000) model. The results indicate that firm size has no significant effect on earnings quality, in contrast to liquidity and accounting conservatism has a significant positive effect on earnings quality. For further research, it is hoped that it can expand the object and the year of research because this study only examines manufacturing companies for the 2015-2019 observation year. For other research, it is expected to add independent variables so that the results are better.